Desain Didaktis Materi Kubus Dan Balok Untuk Mengatasi Kesulitan Penalaran Matematis Siswa SMP - Louise M. Saija; Supriyadi Purba (LPPM Universitas Advent Indonesia, 2023)
This research is based of the lowness the Junior High School students’ mathematical reasoning ability at the Cube and Cuboid material. The research method used is didactical design. The first step of this research was to diagnose the Junior High School student’s difficulties in mathematical reasoning. The test was done towards 24 students at SMP Advent II Setiabudhi and 11 students at SMP Advent Parongpong. The result of the diagnostic test shows that the students had difficulties in Mathematical reasoning of Cube and cuboid material, difficulty in determining the spot of the line in the cube and cuboid that made, difficulty in doing the mathematical manipulation, difficulty in arranging the the prove of the cube and cuboid concept, difficulty in checking the argument validation, and difficulty in making a pattern for a generalization. Based on the difficulties of the students’ mathematical reasoning, the didactical design of learning was made with the purpose to overcome the Junior High Scholl students’ mathematical reasoning difficulties, that are: Give the steps to determine cuboid nets, adding more examples which has mathematical manipulation in it, give more complete proof for cube area using nets with colors, using graphs to help in making generalization, give example for checking arguments validities, and give example to determine the nth pattern.